MENGUKUR KINERJA KEUANGAN BERDASARKAN RASIO PERBANKAN SYARIAH MASA PANDEMI COVID-19 DI INDONESIA - Chandra, Ade; Yunita, Irma (Jurnal Daya Saing, 2023)
Measuring the financial performance of Sharia banking or Islamic banking namely Islamic Commercial Banks (BUS), Islamic Business Units (UUS) and Islamic Rural Banks (BPRS) during the Covid-19 Pandemic in Indonesia using quantitative methods through financial ratios namely ROA, NPF, FDR and REO since March 2020 to August 2022. Data based on the Financial Services Authority's Sharia Banking Statistics from 13 BUS, 20 UUS and 166 BPRS. The results of the study found that during the Covid-19 pandemic, Islamic Banking Financial Ratios, namely ROA ranked 1st and higher at UUS, NPF ranked 1st lower at UUS, FDR ranked 2nd lower at BUS and REO ranked 1st lower at UUS. Islamic banking financial performance during the Covid-19 pandemic in Indonesia based on financial ratios was better at UUS, followed by BUS and BPRS. This shows that Islamic Banking in Indonesia, especially UUS, is able to adapt well to the Covid-19 pandemic so that financial performance is on target.